Flavor-Enhanced Modulation of Cerebral Blood Flow during Gum Chewing - Hasegawa, Yoko; Tachibana, Yoshihisa; Sakagami, Joe; Zhang, Min; Urade, Masahiro; Ono, Takahiro (PloS one, 2013)
Flavor perception, the integration of taste and odor, is a critical factor in eating behavior. It remains unclear how such sensory signals influence the human brain systems that execute the eating behavior. WE TESTED CEREBRAL BLOOD FLOW (CBF) IN THE FRONTAL LOBES BILATERALLY WHILE SUBJECTS CHEWED THREE TYPES OF GUM WITH DIFFERENT COMBINATIONS OF TASTE AND ODOR: no taste/no odor gum (C-gum), sweet taste/no odor gum (T-gum), and sweet taste/lemon odor gum (TO-gum). Simultaneous recordings of transcranial Doppler ultrasound (TCD) and near infrared spectrometer (NIRS) were used to measure CBF during gum chewing in 25 healthy volunteers. Bilateral masseter muscle activity was also monitored. We found that subjects could discriminate the type of gum without prior information. Subjects rated the TO-gum as the most flavorful gum and the C-gum as the least flavorful. Analysis of masseter muscle activity indicated that masticatory motor output during gum chewing was not affected by taste and odor. The TCD/NIRS measurements revealed significantly higher hemodynamic signals when subjects chewed the TO-gum compared to when they chewed the C-gum and T-gum. These data suggest that taste and odor can influence brain activation during chewing in sensory, cognitive, and motivational processes rather than in motor control.